Exploring LGBT2Q+ Intracategorical Factors in Mental Health Service Utilization: Differences in Gender Modalities, Sexual Orientations, and Ethnoracial Groups in Canada. - Tse, Samson; Chee, Kenny; Coleman, Todd. A.; Coulombe, Simon; Travers, Robb (Community Mental Health Journal, 2024)
LGBT2Q+ (lesbian, gay, bisexual, transgender, Two-Spirit, queer, plus) Canadians face minority stressors that lead to higher mental health inequalities such as worse self-reported mental health and increased risk of mental health issues when compared to their heterosexual/straight and cisgender counterparts. However, there are within-group (intracategorical) differences within a community as large as LGBT2Q+ peoples. Guided by the Andersen Model of Healthcare Utilization, we sought to explore intracategorical differences in LGBT2Q+ Canadian predisposing, enabling, and need factors in mental health service utilization within the past year. Using data from the 2020 LGBT2Q+ Health Survey (N = 1542), modified Poisson logistic regression found that more polysexual respondents and trans/gender-diverse respondents were more likely to have utilized mental health services within the past year than their gay, lesbian, and cis male counterparts. As well, compared to White respondents, Indigenous respondents were more likely to have utilized mental health services, while other racialized respondents were associated with less utilization. Backwards elimination of Andersen model of healthcare utilization factors predicting mental health service utilization retained two predisposing factors (ethnoracial groups and gender modality) and two need factors (self-reporting living with a mood disorder and self-reporting living with an anxiety disorder). Results suggest that polysexual, trans and gender-diverse, and racialized LGBT2Q+ peoples have an increased need for mental health services due to increased specific minority stressors that cisgender, White, monosexual peoples do not face. Implications for healthcare providers are discussed on how to improve service provision to LGBT2Q+ peoples.